2015
DOI: 10.1093/mmy/myv045
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcus neoformansin the respiratory tract of squirrels,Callosciurus finlaysonii(Rodentia, Sciuridae)

Abstract: Cryptococcosis is a fungal disease acquired from the environment, for which animals may serve as sentinels for human exposure. The occurrence of Cryptococcus spp. in the respiratory tract of 125 squirrels, Callosciurus finlaysonii, trapped in Southern Italy, was assessed. Upon examination of nasal swabs and lung tissue from each individual, a total of 13 (10.4%) animals scored positive for yeasts, 7 for Cryptococcus neoformans (C.n.) (5.6%) and 6 for other yeasts (4.8%). C.n. was isolated from the nostrils and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…neoformans cultured from the lung and nasal cavity, respectively. 17 We do not possess data concerning the immunocompetence of rodents included in our study, but we assumed that in nature, clinically diseased animals are disabled and therefore more likely to be killed by predators or starvation. Therefore, trapped animals are more likely to be healthy.…”
Section: Discussionmentioning
confidence: 99%
“…neoformans cultured from the lung and nasal cavity, respectively. 17 We do not possess data concerning the immunocompetence of rodents included in our study, but we assumed that in nature, clinically diseased animals are disabled and therefore more likely to be killed by predators or starvation. Therefore, trapped animals are more likely to be healthy.…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen clinical isolates were from human patients with hematological disorders (n ϭ 5), cystic fibrosis (n ϭ 6), or lung disease (n ϭ 5) admitted to different wards of Azienda Ospedaliera-Universitaria, Ospedale Policlinico Consorziale di Bari, between September 2015 and March 2016. Fourteen isolates were from the respiratory tract of squirrels (Callosciurus finlaysonii; Basilicata, Southern Italy) trapped during a campaign to control allochthonous wildlife populations (13). Twelve isolates were from the environment of laying hen farms (14).…”
Section: Isolatesmentioning
confidence: 99%
“…This could reflect the ability of VNIV isolates to tolerate lower temperature better than VNI and C. gattii VGI isolates as previously reported (Cogliati et al, 2017). Other authors reported the isolation of this yeast in the nostrils of squirrels living in the Appenine area of Calabria (Iatta et al, 2015). All together these data confirm that VNIV isolates are able to survive in the European areas with a sub-continental climate (Cogliati et al, 2017).…”
Section: Discussionmentioning
confidence: 95%